Towards tacit knowledge mining within context: Visual cognitive graph model and eye movement image interpretation. (November 2022) - Yu, Weiwei; Jin, Dian; Cai, Wenfeng; Zhao, Feng; Zhang, Xiaokun
Highlights: Modeling operator's attention allocation within task scenario context via eye movement image. Quantitatively analysis of tacit knowledge via indicators derived from graph theory. Demonstrating that the method can reveal the knowledge hidden in visual information. Applications of tacit knowledge in novice operator training and interface design. Abstract: Visual attention is one of the most important brain cognitive functions, which filters the rich information of the outside world to ensure the efficient operation of limited cognitive resources. The underlying knowledge, i.e., tacit knowledge, hidden in the human attention allocation performances, is context-related and is hard to be expressed by experts, but it is essential for novice operator training and interaction system design. Traditional models of visual attention allocation and corresponding analysis methods seldomly involve task contextual information or present the tacit knowledge in an explicit and quantified way. Thus, it is challenging to pass on the expert's tacit knowledge to the novice or utilize it to construct an interaction system by employing traditional methods. Therefore, this paper first proposes a new model called the visual cognitive graph model based on graph theory to model the visual attention allocation associated with the task context. Then, based on this graph model, utilize the data mining method to reveal attention patterns within context to quantitatively analyze the operator's tacit knowledge during operation tasks. We introduced three physical quantities derived from graph theory to describe the tacit knowledge, which can be used directly to construct an interaction system or operator training. For example, discover the essential information within the task context, the relevant information affecting critical information, and the bridge information revealing the decision-making process. We tested the proposed method in the example of flight operation, the comparison results with the traditional eye movement graph model demonstrate that the proposed visual cognitive model can compromise the task context. The comparison results with the statistical analysis method demonstrate that our tacit knowledge mining method can reveal the underlying knowledge hidden in the visual information. Finally, we give practical applications in the examples of operator training guidance and adaptive interaction system. Our proposed method can explore more in-depth knowledge of visual information, such as the correlations of different obtained information and the way operator obtains information, most of which are even not noticed by operators themselves.